1986
DOI: 10.1007/bf00006457
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of Lymnaea peregra (Gastropoda: Pulmonata) in the Leicester canal, U.K., with an estimate of annual production

Abstract: A population of Lymnaeaperegra (Muller) in the Leicester canal, U.K. was sampled quantitatively to determine the life cycle, growth rate and production. The population was shown to be univoltine with a period of egg laying in late spring and very little overlap of generations. Growth rates of 2.41 and 2.86 mm per 4 week period were recorded between June and October in 1978 and 1980 respectively. The winter growth rate during 1980-81 was 0.35 mm per 4 week period.Production by the 1980-81 cohort was estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
6
0
3
Order By: Relevance
“…About a quarter of the lake surface dries over the summer and the shore is muddy, shallow and vegetated; both snail forms are present here. Lymnaeu peregra reproduce in early spring at the Seealpsee, as elsewhere (Bronmark, Rundle & Erlandsson, 1991;Gaten, 1986), and have a univoltine life cycle.…”
Section: The Sampling Sitementioning
confidence: 54%
See 1 more Smart Citation
“…About a quarter of the lake surface dries over the summer and the shore is muddy, shallow and vegetated; both snail forms are present here. Lymnaeu peregra reproduce in early spring at the Seealpsee, as elsewhere (Bronmark, Rundle & Erlandsson, 1991;Gaten, 1986), and have a univoltine life cycle.…”
Section: The Sampling Sitementioning
confidence: 54%
“…Lymnaeu peregra reproduce in early spring at the Seealpsee, as elsewhere (Bronmark, Rundle & Erlandsson, 1991;Gaten, 1986), and have a univoltine life cycle.…”
Section: The Sampling Sitementioning
confidence: 92%
“…has a wide range of environmental tolerance, with a pH tolerance range from 5.8 to 9.9, and prefers calm, shallow water environments, such as lakes, ponds and slow‐flowing rivers (Økland ). Its life span is about 1 year (Young ; Glöer ); shell growth occurs mainly during summer and is slow in winter (Gaten ); and protozoa, weeds, cyanobacteria, chlorophyta and diatoms constitute its primary diet (Knecht & Walter ; Gittenberger et al . ).…”
mentioning
confidence: 99%
“…Young (1975) considered that both cercarial and metacercarial infections in molluscs from the Worcester-Birmingham Canal are important factors in structuring the host community by influencing reproduction (cercarial infections) and mortality (metacercarial infections). Gaten (1986) demonstrated how high cercarial prevalences significantly reduced the density of mature, fertile Lymnaea peregra in the Leicester Canal. He found that no eggs were produced by collected infected snails and calculated, in a single month, that a mature snail population of 18.91 snail per m )2 with a 37.7% cercarial prevalence only contained a breeding population of 11.78 snails per m )2 .…”
Section: Discussionmentioning
confidence: 98%
“…The extensive British canal system is an excellent ecosystem for freshwater trematodes with a wide diversity of species (Young, 1973(Young, , 1974Diaz Diaz, 1976) and high prevalences of both cercarial and metacercarial infections (Young, 1973(Young, , 1975Gaten, 1986) in the molluscan populations. The present study shows that the sampled stretch of the Basingstoke Canal in Surrey in 1970 also contained a comparable diverse and prevalent trematode fauna, and therefore, by association, also contained a diverse guild of aquatic organisms acting as hosts.…”
Section: Discussionmentioning
confidence: 99%